Precise Measurement of Worm and Worm Gear based on Laser Displacement Sensor - Hao Zi; Yun Peng; Yuegang Chu; Yuhan Shen; Aiping Song (Jixie chuandong)
On the basis of analyzing the characteristics of the current measuring technology of worm wheel and worm， a non-contact measurement based on laser displacement sensor and corresponding calculation method of tooth profile and pitch deviation were put forward. A comprehensive measuring device for worm wheel and worm is built to realize the collection of non-contact data. Through the comparison and analysis of the ideal tooth profile model of the worm and worm and the smoothing curve of the fitting point， the deviation of tooth profile and pitch are obtained. Through this method， the measuring process of worm wheel and worm can be effectively simplified and the accuracy and efficiency of measurement can be improved.